A New Co-Crystal of Synthetic Drug Rosiglitazone with Natural Medicine Berberine: Preparation, Crystal Structures, and Dissolution - Xiaoshu Guan; Lan Jiang; Linhong Cai; Li Zhang; Xiangnan Hu (Molecules, 2020)
A co-crystal of rosiglitazone (Rsg) with berberine (Bbr), Rsg-Bbr, was prepared by the solvent evaporation method and characterized. The results showed that the electrostatic attraction existed between the nitrogen anion of rosiglitazone and the quaternary ammonium cation of berberine, and C-H···O hydrogen bonds were formed between Rsg and Bbr. In the crystal structure, rosiglitazone molecules stack into a supramolecular layer through π-π interactions while π-π interactions between berberine cations also result in a similar layer. The co-crystal presented a low moisture adsorption curve in the range of 0−95% relative humidity values at 25 °C. The improved dissolution rate of rosiglitazone in pH = 6.8 buffer solution could be achieved after forming co-crystal.